The Effectiveness of Online Based Learning in Universities During the Covid-19 Pandemic - Dwikurnaningsih, Yari; Waruwu, Marinu (Universitas Pendidikan Ganesha, 2021)
The Covid-19 pandemic has had an impact on the management of learning in universities. Face-to-face learning has shifted to online-based learning. This study aims to analyze the effectiveness of online-based learning in higher education in terms of aspects of planning, implementation, evaluation, constraints and strategies towards new habits. The research method used quantitative-qualitative descriptive. Data collection techniques used interviews and open-closed questionnaires, the results of which were processed qualitatively by using Miles and Huberman's qualitative data analysis model and quantitative data analysis using mean, categorization and percentage calculations. The population of this study was 1,117 students, while the sample was taken randomly as many as 366 people. Interviews were conducted on 9 lecturers. The results of this study indicate that 1) planning, implementation and evaluation of online based learning get an assessment with a good category, 2) online based learning obstacles can be overcome with a blended learning model strategy, practical courses are carried out face-to-face, choosing materials and courses online, online learning is done through virtual face-to-face, attitude assessment using various instruments, and lecturers giving assignments according to the number of credits for the course. Thus, online based learning in higher education needs to be improved through blended learning models, face-to-face practical courses, attitude assessment instruments with various alternatives, selection of materials and courses online or offline and assignments according to the number of credits.